2007
DOI: 10.1007/s00428-007-0413-8
|View full text |Cite
|
Sign up to set email alerts
|

Serrated polyps of the colorectum: is sessile serrated adenoma distinguishable from hyperplastic polyp in a daily practice?

Abstract: The distinction between serrated polyps of the colon is complex, particularly between hyperplastic polyps (HP) and sessile serrated adenomas (SSA). Recent data show that SSA might be the precursors of serrated colonic cancers, underlining the necessity of identifying them. We characterized the demographic and pathologic characteristics of 102 serrated lesions among 321 polyps of the colorectum and determined if SSA can be microscopically distinguished from HP in biopsy material of a daily practice. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 30 publications
5
61
1
3
Order By: Relevance
“…SSA represents 10% of all colonic polyps and around 20% of all serrated lesions (6). In this series, which included only polyps with serration, 3% and 16% of lesions were classified as SSAs by pathologist 1 and pathologist 2, respectively, which was consistent with the literature (14). These are significant percentages, thus failing to accurately diagnose these lesions represents an incorrect assessment of CRC risk for some patients, with consequences for CRC screening and post-polypectomy follow-up programs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…SSA represents 10% of all colonic polyps and around 20% of all serrated lesions (6). In this series, which included only polyps with serration, 3% and 16% of lesions were classified as SSAs by pathologist 1 and pathologist 2, respectively, which was consistent with the literature (14). These are significant percentages, thus failing to accurately diagnose these lesions represents an incorrect assessment of CRC risk for some patients, with consequences for CRC screening and post-polypectomy follow-up programs.…”
Section: Discussionsupporting
confidence: 89%
“…No study has specifically assessed the influence of the sampling method on diagnostic agreement; therefore no comparisons can be done. However, other authors have shown that the classification of serrated lesions is more difficult to apply in superficial and tangentially cut lesions, and in small and fragmented lesions (14), while an en-bloc excised lesion is easier to orientate and diagnose.…”
Section: Discussionmentioning
confidence: 99%
“…28 Because HPs and SSAs are common findings in HPS and have been shown to be difficult to differentiate microscopically, all serrated polyps were included in the criteria. [31][32][33][34] Patients with a known germline APC mutation or a bi-allelic MUTYH mutation were excluded from the study. The study was conducted in accordance with the research code of the institutional medical ethical committee on human experimentation of the Academic Medical Center and in agreement with the Helsinki Declaration of 1975 as revised in 1983.…”
Section: Patientsmentioning
confidence: 99%
“…17,18 Owing to sampling issues, poor specimen orientation and a significant interobserver variation among pathologists, [19][20][21][22] the differential diagnosis of microvesicular hyperplastic polyps vs sessile serrated adenomas/polyps can be very challenging or even impossible. Especially, if we consider that for the differential diagnosis of microvesicular hyperplastic polyp vs sessile serrated adenoma/polyp, the presence of the appropriate morphologic criteria in just one crypt is considered as sufficient.…”
mentioning
confidence: 99%